2007
DOI: 10.1071/sh07018
|View full text |Cite
|
Sign up to set email alerts
|

Male sex work and HIV risk among young heroin users in Hanoi, Vietnam

Abstract: The present study describes complex drug and sexual risk in a group of male sex workers (n=79) who were recruited in the context of a larger study of young heroin users in Hanoi, Vietnam (n=1270). Male sex workers were significantly more likely than male non-sex workers to be migrants (P<0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 13 publications
2
35
0
Order By: Relevance
“…Drug use has a strong link with male-to-male commercial sex. 22,23 As shown in our study, MSM who self-identified as heterosexual males may play an important role in acting as a bridge for HIV/STIs from high-risk populations to the general population because of their prevalent bisexual behaviors and low condom usage in both male and female partnerships. Similar to findings among Cambodian MSM, 24 our results strongly indicated that having unprotected sex with an FSW significantly increased the likelihood of HIV infection among Vietnamese MSM.…”
Section: Discussionmentioning
confidence: 91%
“…Drug use has a strong link with male-to-male commercial sex. 22,23 As shown in our study, MSM who self-identified as heterosexual males may play an important role in acting as a bridge for HIV/STIs from high-risk populations to the general population because of their prevalent bisexual behaviors and low condom usage in both male and female partnerships. Similar to findings among Cambodian MSM, 24 our results strongly indicated that having unprotected sex with an FSW significantly increased the likelihood of HIV infection among Vietnamese MSM.…”
Section: Discussionmentioning
confidence: 91%
“…For example, Scott et al note that sex workers under the legal age of consent, migrants, and particularly undocumented migrants, may be more vulnerable to manipulation, blackmail, or threats from clients. Those working in public spaces are at significantly higher risk of violence, particularly the less organized male sex workers who may rely more on unmediated transactions (ie, not via a medium which allows for screening such as internet, telephone or a third party) and chance encounters (45). Those who work in groups are also less likely to suffer victimization than those who work alone or in isolated settings: thus, violence against male sex workers is heavily contextual.…”
Section: Male Sex Workersmentioning
confidence: 97%
“…Clatts et al (45), in their study of heroin-using male sex workers in Hanoi, Vietnam, noted that meanings for same-sex exchange may be different from western cultures. Such meanings may not be economic or "cost-benefit" based and may include opportunities for contact with someone from a different culture, a chance to practice language skills, or based on the expectation not of immediate payment but rather deferred material rewards.…”
Section: Male Sex Workersmentioning
confidence: 99%
“…We assessed a range of sexual risk-taking behaviours, including the number of clients in past week, using a condom with a regular (unpaid) sexual partner, condom use with their last client (paid sexual encounter), anal or oral sex practices with clients, and involvement in other paid sexual activities (e.g., masturbation and letting a client take photos or videos). Because condom use during the last paid encounter is the most commonly used outcome in research with sex workers, we utilised 'condom use with last client' as the dependent variable for all bivariate and multivariate logistic regression models (Williams et al 2006, Clatts et al 2007). …”
Section: Study Variables Dependent Variable Sexual Risk Behavioursmentioning
confidence: 99%